Negotiating Race and Gender: An Intersectional of Hidden Figures (2016) - Ratria Inca Ristiyaningsih; Maya Sekartaji (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This article examines how race and gender intersect to shape the lived experiences of African American women in Hidden Figures (2016), focusing on the strategies of negotiation and resistance employed within institutional constraints. Using qualitative textual analysis, this study applies Kimberlé Crenshaw’s Intersectionality Theory as the primary analytical framework, highlighting how systemic discrimination operates through organizational structures, social norms, and cultural expectations. The findings reveal that the female protagonists exercise agency through professional competence, intellectual problem-solving, and collective solidarity, which allow them to challenge exclusionary practices and assert visibility in a historically segregated workplace. By emphasizing the dynamics of negotiation and resistance, this study contributes to feminist, race, and cultural studies, demonstrating how intersectionality can illuminate both oppression and the strategies marginalized women employ to navigate and contest structural inequalities.